Controlled Frame for Operator in Hilbert c∗-Modules. (14th March 2022) - Labrigui, Hatim; Touri, Abdeslam; Rossafi, Mohamed; Kabbaj, Samir
Abstract : In this study, we will introduce a new concept, which is a controlled K -operator frame for the space of all adjointable operators on a Hilbert A -module ℋ which denoted End A ∗ ℋ, where A is a C ∗ -algebra. Also, we establish some results of the controlled K -operator frame in End A ∗ ℋ . The presented results are new and of interest for people working in this area. Some illustrative examples are provided to advocate the usability of our results.